The effect of innovation attributes and taxpayers experience on the interest of the use of online tax filing system on individual taxpayers in Surabaya - Dody Setia Rahman; Triana Mayasari (STIE Perbanas Surabaya, 2015)
So far, the reform in tax payment with its self-assessment system can provide a solu-tion required for better tax payment and bring public services to the community-oriented. However, the self-assessment system has shown a lot of weaknesses that make taxpayer services not optimal. The purpose of this study is to determine the factors that affect the interest of the use of online tax filing system on individual taxpayer in the Tax Office Pratama Surabaya City Karangpilang. The factors used as independent variables in this study are innovation attributes consisting of relative advantage, compatibility, complexity, trialability, observability and taxpayers experience. As many as 100 respondents comprising individual taxpayers are selected as respondents in the study. The results show that there is significant effect between innovation attributes consisting of relative advantage, compatibility, complexity, trialability, observability and taxpayers experience on the interest of the use of online tax filing system. And the researcher finds that most significant effect on the interest of the use of online tax filing system is compability.